COMPLEMENTARITY OF DIFFERENT STRATEGY BY SUPPORTING THE DEVELOPMENT OF THE DANUBE REGION - Jovanović, Sonja; Radukić, Snežana (Economics of Agriculture, 2011)
The growing institutional, economic and social interdependence requires collective action to go to meet the challenges of sustainable development. The concept of sustainable development of the European Union is based on balanced economic growth and macroeconomic stability, a highly competitive market economy, aiming at full employment, social progress and a high level of protection and improvement of environmental quality. The subject of analysis in this paper is to point out the interconnectedness of goals and priorities of several important strategies for sustainable development of European countries. Special emphasis is on linking strategy for the Danube region with other strategies in an integrated approach to the development of the region, coordination of sectorial policies and coordination at all levels. Strategy for the Danube region contributes to achieving the objectives of rural development, as this paper points out. The methods to be used in the work are comparative method, analysis and synthesis.